Mechanical properties of sisal fibre-reinforced polymer composites: a review. Issue 1 (2nd January 2016) - Ibrahim, Idowu David; Jamiru, Tamba; Sadiku, Emmanuel R.; Kupolati, Williams Kehinde; Agwuncha, Stephen C.; Ekundayo, Gbenga
Abstract: There has been a growing interest in the utilization of sisal fibres as reinforcement in the production of polymeric composite materials. Natural fibres have gained recognition as reinforcements in fibre polymer–matrix composites because of their mechanical properties and environmental friendliness. The mechanical properties of sisal fibre-reinforced polymer composites have been studied by many researchers and a few of them are discussed in this article. Various fibre treatments, which are carried out in order to improve adhesion, leading to improved mechanical properties, are also discussed in this review paper. This review also focuses on the influence of fibre content and fabrication methods, which can significantly affect the mechanical properties of sisal fibre-reinforced polymer composites.